Sakha language and education in a social, cultural and political context - Ventsel, Aimar; Struchkova, Natal’ia (Sociolinguistic Studies, 2015)
This paper analyses the language situation in the Republic of Sakha, Russian Far East. Due economic, social and political processes, Sakha language occupies at least two niches in the society – as a language of disadvataged low social strata and as a language for the national elite. The paper demonstrates that one language can have several social positions simultaneously in an envirounment where multiple social, economic and political factors determe the social and cultural identity of its speakers. The role of education and access to the good quality schools is in the Republic of Sakha more crucial in creating a social status of the speakers and their language than official national language policy. Our paper is critical to sociolinguistic theories of “killer languages”, language utility, code switching and other theories that see a language group as homogenous body acting as a unit. The Sakha case demonstrates that in reality language speakers do not form a coherent group and the status of their language can vary according to the social position of the speakers. The paper also shows that processes we call “elitarisation” and “lumpenisation” of the language are intermingled and that people can move from one language strata into another using various strategies. As a result we conclude that in multilingual environment, education system is important as an institution that affects people’s life paths via networks they are able to establish in school or social groups they study with.